CONTRIBUTIONS TO THE ABRASIVE WATERJET MACHINING OF PARTS (Nonconventional Technologies Review, 2019)
The requirement for increasing the efficiency of waterjet machining processes such as to improve surface quality and dimensional precision has led to research with major global contributions. Abrasive waterjets are increasingly used in modern industry, despite the challenge of explaining the extremely complicated phenomena underlying the machining process. The paper presents a series of aspects concerning the mechanics of cutting in abrasive waterjet machining. Based on the imposed conical model of the abrasive grain a methodology is put forward for the computation of the necessary work pressures in the case of waterjet boring and cutting.
Keywords: abrasive waterjet; abrasive boring; abrasive cutting; work pressure